1977
DOI: 10.1111/j.1365-2184.1977.tb00137.x
|View full text |Cite
|
Sign up to set email alerts
|

A Deficiency of Hematopoietic Stem Cells in Steel Mice

Abstract: In the present study, population sizes of high self‐renewal potential stem cells, i.e. colony forming units (CFU), and low self‐renewal potential stem cells, i.e. transient endogenous colony forming units (TE‐CFU) in Sl/Sld mice and their normal congenic littermates were measured and compared. By correcting for differences in the seeding efficiency ‘f’, it was possible to demonstrate that Sl/Sld mice suffer a deficiency of both stem cell populations. Therefore, it is concluded that the defective stromal tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…It has been suggested that there is a strong stimulus for differentiation in Sl/Sld mice, which sustains a normal splenic CFU-s content despite the apparent defect of the splenic stroma (Wolf, 1974;Bernstein et al, 1968;McCarthy, Ledney & Mitchell, 1977;Harrison, Malathi & Silber, 1975;McCarthy, 1977). We propose that this strong stimulus may be absent in SlJ/+ mice, due to the mild nature of the anaemia, resulting in a decreased CFU-s population, which is most evident in the spleen.…”
Section: Discussionmentioning
confidence: 74%
“…It has been suggested that there is a strong stimulus for differentiation in Sl/Sld mice, which sustains a normal splenic CFU-s content despite the apparent defect of the splenic stroma (Wolf, 1974;Bernstein et al, 1968;McCarthy, Ledney & Mitchell, 1977;Harrison, Malathi & Silber, 1975;McCarthy, 1977). We propose that this strong stimulus may be absent in SlJ/+ mice, due to the mild nature of the anaemia, resulting in a decreased CFU-s population, which is most evident in the spleen.…”
Section: Discussionmentioning
confidence: 74%
“…Since it has been shown that erythropoietin increases the cycling of CFUs within 18 hr of its administration (Guzman & Lajtha, 1970), the possibility remains that greater stem cell cycling may have also been evident in these mice with elevated erythropoietin levels. Along these lines, McCarthy, Ledney & Mitchell (1977) have also shown that rapidly cycling S1/Sld marrow CFUs show lower seeding than non-cycling CFUs from their +/+ littermates. Worton et al (1969b) demonstrated by velocity sedimentation that large normal marrow stem cells were characterized by a lower seeding efficiency (about 8.5%) than small cells (about 16%), although the variance in their data precluded the establishment of any significant difference.…”
Section: Discussionmentioning
confidence: 84%
“…Thrombopoietin (TPO) and stem cell factor (SCF) are two cytokines that are indispensable for the maintenance of quiescent self-renewing adult HSCs in the bone marrow niche (129133) ( Figure 3 ). The humanization of the gene encoding TPO by knockin replacement in the Rag2 −/− Il2rg −/− background led to a significant increase in the number and the maintenance of functional long-term HSCs, as demonstrated by immunophenotypic characterization and enhanced capacity to repopu-late secondary recipients, respectively.…”
Section: Remaining Limitations and The Next Generation Of Hhls Micementioning
confidence: 99%